KAJIAN SARUNG SAMARINDA DARI PRESPEKTIF PEMANGKU KEPENTINGAN - Purwadi Purwadi Purwadi (KINERJA, 2015)
Sarong Samarinda is one of the peculiarities of East Kalimantan in addition amplang, batik Kaltim, saber, engraving dayak and others. Gloves existence, at least, helped make this glove into a 'trademark' Samarinda so that visitors from outside Borneo is more familiar with the name of East Kalimantan. The study results show that (1) Samarinda Seberang is the center of Samarinda Sarong weaving craft. (2) Segment Samarinda sarongs market is limited to the upper middle level or tourists both domestic and foreign countries. (3) Gloves loom Samarinda has a unique style and excellence in terms of comfort when worn (4) There are limitations of the technology used to manufacture gloves Samarinda (5) Until now perngrajin Sarong Samarinda work incidental (6) Another problem faced by the glove businessman is lack of government's role in terms of capital, marketing and promotion (7) There is a pattern and a system integrated with the economic sectors of tourism development in the city of Samarinda in East Kalimantan in particular and in generalKeyword: Samarinda sarongs, Stakeholders